Spatiotemporal distribution and shoaling behaviour of fish (Časoprostorová distribuce a hejnové chování ryb) - Sajdlová, Zuzana (Jihočeská univerzita, 2019)
The dissertation thesis is focused on pelagic fish distribution in the large freshwater bodies and the main factors affecting it. Paper 1 describes fish behaviour in a mouth of a midwater trawl during different day time periods as fish activity may importantly affect abundance estimates of the sampled fish stock. Acoustically recorded avoidance behaviour in a vertical direction is described. The second part of the thesis refers to the diel distribution and behaviour of the pelagic fry communities with a particular focus on the vertically migrating bathypelagic percid fry that occupy open water during early ontogeny. Paper 2 shows that the vertically migrating community can create a dominant part of fry assemblages in the reservoir, which is in contrast to many previous observations of an usually prevailing non-migrating epipelagic community. At their day refuge, bathypelagic percid fry (BPF) created dense shoals whose physical parameters are described. Paper 3 for the first time demonstrates that vertical shifts of BPF were under direct light control, hence were not a genetically fixed behaviour. A unique large-scale field experiment with the simultaneously operating up-looking and down looking transducers was carried out under artificially controlled light regime. Moreover effect of predation as the main ultimate cause of vertical shifts is discussed. The introductory part of the thesis opens with the current possibilities of assessing distribution and behaviour of fish in the open water. Benefits of shoaling/schooling behaviour during defence against predators, foraging and learning abilities of fish are mentioned and some implications of fish behaviour on the fish capture process are pointed out. The second chapter deals with the diel shifts between habitats that belong among the most common activities of fish. However, distribution of fish varies also over the long temporal scale and currently has been strongly affected by changing climate. Therefore, the main affects of climate change on the world´s fish populations are introduced using examples from both freshwater and marine environment.
Spatiotemporal distribution and shoaling behaviour of fish
Keywords: fish behaviour; distribution; shoals; hydroacoustic; trawling; reservoir; fish behaviour; distribution; shoals; hydroacoustic; trawling; reservoir